Features of functioning of the fruit and vegetable products market in Russia - I. A. Aksenov (Овощи России)
Relevance and methods. The structure of the food market is represented by various types of products, of which the largest share is in the fruit and vegetable sector. Given the tense political situation in the world and the establishment of barriers in foreign trade, agriculture is a strategically important sector of the Russian economy. Today, the fruit and vegetable branch of the Russian economy does not fully satisfy the population’s needs for fruits and vegetables. This is evidenced by the fact that the domestic market does not provide the population with high-quality vegetables and fruits, creates favorable conditions for filling it with foreign goods, which make up about 35% of the consumer basket of Russians. All this leads to the need for additional analysis to identify trends in the Russian market of fruits and vegetables and identify priority areas for its development. The purpose of the article is to identify the features of the functioning of the fruit and vegetable market in Russia. The study was based on statistics from the customs authorities of the Russian Federation on the import and export of fruits and vegetables, as well as the Federal State Statistics Service on production, consumption of fruits and vegetables in Russia. The article discusses the features of the functioning of the fruit and vegetable market in Russia. The key factors that influence the development of the market of fruits and vegetables at the present stage are determined.Results. As a result of analysis of the state of the market of fruits and vegetables in Russia in 2011-2020. it can be stated that the fruit and vegetable market is experiencing difficult times due to the sanctions policy of the EU and the USA and the low level of material, technical and logistics base in Russia. The advantages of the market of fruits and vegetables during the period of antiRussian sanctions are reflected. Groups of problems of functioning of the market of fruits and vegetables are revealed. Based on the identified problems of the fruit and vegetable market, methods for solving them are proposed based on the best practices of the European Union. The article focuses on the development of the market for fruits and vegetables in Russia. The proposed solutions and development directions are substantiated by specific figures of economic efficiency.